THE HUMAN PERSON FROM SRAMANA PERSPECTIVES - Sekhar, Vincent (Journal of Dharma, 1996)
'Sramana perspectives are different from and, at times opposed to, Vedic and Brahmana perspectives. 'Sramana' means austerity and it can also imply an attitude of equanimity (samatá bhåva). 'Sramananas are those whose views and life-style pertain to an ascetic ethos (Nivrttimáraga) where renunciation, detachment, mora. discipline etc.l play an important role, while Vedic and the Brahmánic views on life are more affirming and liberal. The 'Sramana history reveals their link with Mohanjodaro and Harappa cultures and, the Indus valley civilization. The ascetic practices ot the Sramanas are indicated in the seals discovered in those areas. The references to 'Sisnadevah in the Vedas bring out the then 'existing religious symbols of worship ('nude deities' referring to the Tirthankaras of the Jains). Some Vedic prayers refer to . those people who were anti-vedic and against ritual sacrifices. Indra is sought for protection from them.